Maximal heart rate does not limit cardiovascular capacity in healthy humans: insight from right atrial pacing during maximal exercise. (2nd December 2013) - Munch, G. D. W.; Svendsen, J. H.; Damsgaard, R.; Secher, N. H.; González‐Alonso, J.; Mortensen, S. P.
Key points During high intensity whole‐body exercise, systemic and contracting skeletal muscle O2 delivery and uptake (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4sqs9g4w" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />V̇O2</alternatives>) are compromised, but the underlying mechanisms remain unclear. We evaluated the effect of a ∼20 beats min−1 increase in heart rate (HR) by right atrial pacing during incremental cycling and knee‐extensor exercise on cardiac output (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4sqs9hj1" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Q̇</alternatives>) and stroke volume (SV). An increase in HR during both exercise modalities did not alter <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4sqs9hgx" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Q̇</alternatives> due to a proportional decrease in SV. The lower SV during atrial pacing in the cycling trial was associated with a diminished cardiac filling pressure, but similar arterial pressure. The results demonstrate that the human heart can achieve a higher HR than observed during maximal exercise, suggesting that HRmax and myocardial work capacity do not limit cardiac performance in trained human subjects. Instead, restrictions in ventricular filling appear to compromise cardiac preload, SV and <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4sqs9hdt" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Q̇</alternatives> at exercise intensities close to <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4sqs9hc8" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />V̇O2 max </alternatives>.